Bringing Order to Chaos Ethically: “Cataloging Code of Ethics” and critical cataloging - Dalila Mirović (Bosniaca)
Goal: The goal of this paper is to address the ethics in cataloging and the concept of critical cataloging, as a sub-movement of critical librarianship, as well as to highlight the intersection of ethics with critical in cataloging. It also provides an overview of the most relevant academic papers, articles, and documents in this field, with a special focus on the Cataloging Code of Ethics, the first comprehensive, collaborative, and internationally accepted Code specific to the profession. This code was published in 2021 by the Cataloging Ethics Steering Committee (CESC), which includes representatives from three library associations from three different countries: the American Library Association (ALA), the Chartered Institute of Library and Information Professionals (CILIP), and the Canadian Federation of Library Associations (CFLA-FCAB). Approach/methodology/design: Using content analysis, this paper presents relevant research on ethical cataloging. Through the methods of comparison, analysis, and synthesis, an inductive approach is used to establish a theoretical framework for the subject of the research. Results: The results show that, particularly in the last two decades, this topic has gained significant attention within the cataloging community. Catalogers, aware of their role in building information architecture, have begun to critically reflect on their profession and articulate the need for a document that provides guidelines for ethical organization of metadata. Social relevance: The research advocates that the power to organize knowledge and the power to name, held by catalogers, must be balanced with professional ethics. A critical approach to the profession and the Cataloging Code of Ethics can aid in this process, which could have positive implications for society as a whole. Originality/value: The originality of this paper lies in its critical examination of a cataloging trend that has not yet been discussed in our region.